Dojrzałość strategii jako przesłanka zarządzania bezpieczeństwem organizacji - rozpoznanie wśród producentów technicznych środków transportu rolniczego = Maturity of the strategy as a premise for organizational safety management - recognition among producers of technical means of agricultural transport - Niewiadomski, Przemysław; Kurzawski, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this work is to attempt to answer the question about the level of maturity in the perception and implementation of strategies created by enterprises operating in the agricultural machinery sector. As part of the project, research was first undertaken to identify the desiderata characterizing the strategy. This required the formulation and implementation of partial tasks, which included, on the one hand, a literature search in direct relation to the research topic (theoretical and design layer), and on the other - in order to determine the level, scope and structure of the strategy maturity desiderata formulated by enterprises - empirical verification, which determined the construction of a research model.
Keywords: samoocena dojrzałości strategii; Zarządzanie strategiczne; weryfikacja modelu badawczego; self-assessment of strategy maturity; strategic management; verification of the research model